Influence of the psoas major and thigh muscularity on 100-m times in junior sprinters - Hoshikawa, Y.; Muramatsu, M.; Iida, T.; Uchiyama, A.; Nakajima, Y.; Kanehisa, H.; Fukunaga, T. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study aimed to investigate how the cross-sectional areas (CSA) of the quadriceps femoris (QF)3, hamstrings (Ham), and psoas major (PM) in junior sprinters are related to mean running velocity (MV100m) calculated from official records of 100-m races.